Supplementary material Article 65677. Tooth row variation in tadpoles of Dendropsophus labialis (Anura: Hylidae: Dendropsophini) and the evolution of oral morphology in the genus - Gustavo A. Ballen (Caldasia)
Appendix S1.1. Dataset for embryos (GS 25 or younger) and referenced as “embryos.csv” in the script. Appendix S1.2. Dataset for larvae (GS 25 or older) and referenced as “larvae.csv” in the script. Appendix S2.1. iter.cor.test.R function needed for the analysis script. Written in R. Appendix S2.2. ontogeny.R script for carrying out the analyses. Appendix S3. Species of Dendropsophus and references describing oral morphology.